Postoperative clinical course and tolerability of a 3% coffee infusion in patients undergoing elective surgery: a prospective descriptive study - Elsy Victoria Rueda Páez; Lennys Carvajal Suárez; Clara Helena Gonzalez Correa (Inge Cuc, 2026)
Introduction: Elective surgeries allow for optimal clinical preparation, unlike emergencies. However, outcomes such as postoperative ileus increase costs and hospital stays. Consequently, non-pharmacological interventions like coffee infusion, rich in caffeine and chlorogenic acid, have been explore. Objective: To describe the postoperative clinical evolution and tolerability of administering a 3% coffee infusion in patients undergoing elective surgeries. Materials and Methods: An observational, descriptive, and prospective study was conducted in 17 adult patients who underwent elective surgery at Hospital San Juan de Dios de Pamplona, Colombia. Patients received three cups of 3% coffee daily starting at the initiation of oral intake. Sociodemographic, anthropometric, and clinical variables were collected, and the presence of symptoms associated with postoperative ileus and hospital length of stay were evaluated Results: Among the participants, 88.3% were women, with a mean age of 42.6 years. Malnutrition was observed in 70.7% of patients, mainly due to excess weight, and 76.5% exhibited cardiovascular risk based on waist circumference. Most surgeries were open procedures (76.5%). No patient developed postoperative ileus, 88.2% had a one-day hospital stay, and no complications associated with coffee consumption were reported. Conclusion: The use of 3% coffee in postoperative patients was safe and associated with absence of illnesses and short hospital stays. Coffee may represent a low-cost, non-pharmacological strategy to support postoperative recovery; however, larger controlled studies are needed to confirm its effectiveness and establish standardized protocols.